Pengetahuan, Sikap, dan Perilaku Remaja di Pulau Lombok Terhadap Isu Pemanasan Global - Wildan Wildan; Aliefman Hakim; Supriadi Supriadi (Postgraduate, University of Mataram, 2020)
This survey research aimed to understand the relationship between knowledge and attitudes of pupils on Lombok Island on the issue of global warming. The research sample of 267 students were randomly drawn from 6 state high schools in Lombok Island. Knowledge data were collected using tests, attitude and behavior data towards global warming were collected using a questionnaire. Data analysis used regression and correlation techniques. This study concluded: (1) there was a relationship between knowledge and the behavior of pupils on Lombok Island on the issue of global warming; (2) There was a relationship between attitude and behavior of pupils on Lombok Island on the issue of global warming; (3) there was a positive relationship between knowledge and attitudes with adolescent behavior on Lombok Island.